2023
DOI: 10.7554/elife.87115
|View full text |Cite
|
Sign up to set email alerts
|

Microhomology-mediated circular DNA formation from oligonucleosomal fragments during spermatogenesis

Abstract: The landscape of extrachromosomal circular DNA (eccDNA) during mammalian spermatogenesis, as well as the biogenesis mechanism remains to be explored. Here, we revealed widespread eccDNA formation in human sperms and mouse spermatogenesis. We noted that germline eccDNAs are derived from oligonucleosomal DNA fragmentation in cells likely undergoing cell death. Interestingly, small-sized eccDNAs are associated with euchromatin, while large-sized ones are preferentially generated from heterochromatin. By comparing… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 59 publications
1
1
0
Order By: Relevance
“…In fact, our study also found that eccDNA is significantly abundant in the TE region, especially in the LTR region. Aligning with the findings reported by Hu et al 32 , our research also uncovered a significant correlation between eccDNAs and DNA Repeats within TEs. This observation suggests the possibility that DNA transposons may undergo circularization, either as an alternative to or concurrently with reintegration into the genome, a hypothesis that warrants further exploration.…”
Section: Discussionsupporting
confidence: 91%
“…In fact, our study also found that eccDNA is significantly abundant in the TE region, especially in the LTR region. Aligning with the findings reported by Hu et al 32 , our research also uncovered a significant correlation between eccDNAs and DNA Repeats within TEs. This observation suggests the possibility that DNA transposons may undergo circularization, either as an alternative to or concurrently with reintegration into the genome, a hypothesis that warrants further exploration.…”
Section: Discussionsupporting
confidence: 91%
“…By driving oncogene overexpression and fostering genetic diversity, eccDNA plays a crucial role in tumor evolution and resistance to therapies [ 6–9 ]. Additionally, eccDNA can influence spermatogenesis and act as innate immunostimulants in normal tissue [ 10 , 11 ]. Due to its structural diversity, functional versatility and variable abundance, investigations into eccDNA shed light on the molecular mechanisms underlying DNA repair pathways, genomic instability and gene expression regulation.…”
Section: Introductionmentioning
confidence: 99%